TRENDS IN BEHAVIOUR OF MODERN FOOD CONSUMERS IN POLAND - Krystyna Świetlik (Polityki Europejskie, Finanse i Marketing, 2020)
The aim of the paper is to present the changes in the level and structure of food consumption in Poland during 2013-2017 from a macro and micro-economic perspective, based on CSO (Central Statistical Office) data gathered from national accounts and household budgets. Analysis of the data showed that in an improved economic climate and significantly improved income situation households changed their preferences both in terms of the amount of food consumed as well as in the structure of consumption. Real expenditure on food increased despite reduced volume in consumption, with more eating out and less self-catering. The increase in the share of highly processed foods and more expensive products in the basket of foods contributed to the stabilisation of the share of expenditure on food as part of total household expenditure.